Leadership in the Context of Applied Ethics. Application of Coaching in the Process of Educating Leaders - Chmielecka, Monika; Boroch, Robert (INSTED: Interdisciplinary Studies in Education & Society, 2017)
In the paper, we discuss the educational potential of coaching as a complementary tool for leadership training. Coaching is treated as a supporting method in the process of learning that must be backed up with some philosophical aspects in virtues that allow building up social leadership competence. Thus, leader virtues, such as loyalty, personal example or duty are discussed as quality issues of the modern leader.